The role of ethics of care messaging in AI crisis communication: examining the interplay role of ethics of care and crisis response strategies on organization-public relationship, organizational reputation and behavioral intention - Choi, Sera, author; Kim, Jangyul, advisor; Sivakumar, Gayathri, committee member; Park, Young Eun, committee member; Hastings, Pat, committee member; Yan, Ruoh-Nan, committee member (Colorado State University. Libraries, 2024)
This dissertation explores the effectiveness of crisis response strategies—specifically denial, excuse, and apology—in the context of artificial intelligence (AI) crises, emphasizing the mediating role of Organization-Public Relationships (OPR) and the moderating impact of ethics of care on organizational outcomes. Utilizing a 3 (crisis response strategies: deny, excuse, apology) x 3 (ethics of care: high vs. low vs. no) between-subjects design, the study examined the influences of different crisis response strategies and levels of ethics of care on OPR outcomes, organizational reputation, and supportive behavioral intentions across a sample of 532 participants. Participants were assigned to one of nine experimental conditions depicting a crisis involving a fictitious company, "Hexxa," portrayed in varying contexts of ethics of care. Data collection was conducted through an online survey platform – Prolific, employing paired samples t-tests, one-way ANOVA, and moderated mediation analysis using PROCESS Model 84. The results revealed that apology strategies significantly improved OPR outcomes and organizational reputation more effectively than denial and excuse strategies. High levels of ethics of care enhanced these outcomes across all response strategies, surpassing effects in low and no ethics of care conditions. Although direct effects of crisis response strategies on organizational outcomes were often non-significant, the incorporation of ethics of care significantly magnified these effects through OPR, underscoring its pivotal role in crisis communication. The findings deepen situational crisis communication theory (SCCT) by illustrating how ethical considerations and organization-public relationships interact to influence organizational outcomes in AI-related crises, advocating a shift towards more ethically nuanced crisis communication approaches. Practically, the results advocate for the prioritization of ethics of care in crisis communication, providing empirical support for its effectiveness in not only mitigating crisis impacts but also in fostering long-term public relationships. The study's findings also reveal the significant, yet differentiated, impacts of low versus no ethics of care approaches, suggesting a threshold effect for ethical considerations in crisis response. These insights yield important implications for practitioners, highlighting that even minimal ethical engagement can significantly influence public perception and behavior. In conclusion, the dissertation posits a call to action for organizations to strategically incorporate ethical considerations within crisis communication frameworks, especially in AI-driven contexts, where socio-technical risks pose unique challenges.
Keywords: behavioral intention; ethics of care; organizational reputation; crisis communication; artificial intelligence; organization public relationship